Comparison of Agar Gel Immunodiffusion Test, Enzyme-linked Immunosorbent Assay and Western Blotting for the Detection of BLV Antibodies - Dolz, Gaby (1999)
An indirect enzyme-linked immunosorbent assay (ELISA) for the diagnosis of bovine leukaemia virus (BLV) infection was developed and compared with the agar gel immunodiffusion test (AGIDT). Western blotting (WB) was used as confirmatory test. ELISA and AGIDT had specificities that were comparable with that of WB, however, ELISA showed a higher sensitivity than AGIDT. The ELISA was useful for screening a large number of samples, whereas WB was important for detecting the antibody response against the individual BLV-proteins. Different types of positive serological reactions were discerned in WB, that correlated with reactions of sera in AGIDT and ELISA. The most important antigen in WB and ELISA was the BLV protein p24, whereas the BLV glycoproteins gp51 and gp30 were of special importance in AGIDT. The relevance of repeatedly testing the antibody response in BLV-infected herds for control and eradication programmes using assays with higher sensitivity than AGIDT was demonstrated.